Self-ignition calculation of diesel spray - Marcic, Milan; Avsec, Jurij; Praunseis, Zdravko; Marcic, Simon; Wensing, Michael; Leipertz, Alfred (SAE Technical Papers, 2012)
This paper describes a computer simulation of Diesel spray formation and the locations of self-ignition nuclei. The spray is divided into small elementary volumes in which the amounts of fuel and fuel vapours, air, mean, maximum and minimum fuel droplet diameter are calculated, as well as their number. The total air-fuel and air-fuel vapour ratios are calculated for each elementary volume. The paper introduces a new criterion for determining self-ignition nuclei, based on assumptions that the strongest self-ignition probability lies in those elementary volumes containing the stoichiometric air ratio, where the fuel is evaporated or the fuel droplet diameter is equal to or lower than 0.0065 mm. The most efficient combustion in regard to consumption and emission will be in those elementary volumes containing stoichiometric air ratio, and fuel droplets with the lowest mean diameters. Measurements of injection and combustion were carried out in a transparent research engine. This engine is a single-cylinder transparent engine based on the AUDI V6 engine, equipped with a Bosch Common Rail Injection System. The optical part of the experimental setup contains two different lasers, while the camera system allows for simultaneously detecting 4 signals: the Mie scattering of the injected fuel, the laser-induced fluorescence (LIF) of fuel and vapour, light emissions from the flame indicating the premixed combustion mode, and flame emissions indicating the diffusion mode. Comparison of the computed points with the highest self-ignition probability and the measured points where self-ignition occurred showed good matching. Copyright © 2012 SAE International.
Created from Fastlane, Scopus look-up